1994
DOI: 10.1139/x94-114
|View full text |Cite
|
Sign up to set email alerts
|

Modifying sexual expression of containerized jack pine by topping, altering soil nitrogen and water, and applying gibberellins

Abstract: The numbers of seed strobili and pollen strobilus clusters and the extent of branch terminal growth were determined on 6-year-old containerized jack pine (Pinusbanksiana Lamb.) trees following modification of the soil nitrogen (N) supply (NH4NO3 at 3, 100, or 300 mg N/L; NO3− at 100 mg N/L; or NH4+ at 100 mg N/L in a nutrient solution), soil water supply (soil water potentials above −20 kPa compared with potentials near −70 kPa), and tree crown size (intact trees outside polythene shelters and lightly versus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Pinus radiata D. Don cuttings produce pollen strobili after 2 years of growth when subjected to nitrogen deficiency (Sweet and Will 1965). We have observed that nitrogen deficiency promotes pollen strobilus production in 5-year-old jack pine seedlings (Fogal et al 1994), and Riemenschneider (1985) reported that short-term soil water deficits enhance seed strobilus production in jack pine seedlings.…”
Section: Introductionmentioning
confidence: 74%
“…For example, Pinus radiata D. Don cuttings produce pollen strobili after 2 years of growth when subjected to nitrogen deficiency (Sweet and Will 1965). We have observed that nitrogen deficiency promotes pollen strobilus production in 5-year-old jack pine seedlings (Fogal et al 1994), and Riemenschneider (1985) reported that short-term soil water deficits enhance seed strobilus production in jack pine seedlings.…”
Section: Introductionmentioning
confidence: 74%
“…However, we suggest that this pattern is among the most interesting results of our analysis and worthy of further investigation. In general, jack pine pollen cone production can increase in response to stress or in response to improved growth conditions (Fogal et al 1994(Fogal et al , 1999Kozlowski and Pallardy 2002;McCullough and Kulman 1991). It would be interesting to know if jack pine trees are becoming more or less stressed over time in central Ontario and why.…”
Section: Discussionmentioning
confidence: 99%